2016
DOI: 10.1007/s10551-016-3363-8
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Managers Leave Their Organization? Investigating the Role of Ethical Organizational Culture in Managerial Turnover

Abstract: The aim of the present longitudinal study was to quantitatively examine whether an ethical organizational culture predicts turnover among managers. To complement the quantitative results, a further important aim was to examine the self-reported reasons behind manager turnover, and the associations of ethical organizational culture with these reasons. The participants were Finnish managers working in technical and commercial fields. Logistic regression analyses indicated that, of the eight virtues investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 85 publications
2
23
0
Order By: Relevance
“…Dai, Chan, & Yee (2018) defines organizational culture as organizational culture is unique characteristics that reflect an organization's goals and values, including assumptions, beliefs, norms, and ideas. Kangas, Kaptein, Huhtala, Lämsä, Pihlajasaari, & Feldt (2018) added that organizational culture is the ethical quality of a work environment, incorporating the experiences, presumptions, and expectations of the organization's members. Marliana (2015) concluded that organizational culture is an organizational value system adopted by members of the organization, which influences the way of working and behaving from the members of the organization.…”
Section: Organizational Culturementioning
confidence: 99%
“…Dai, Chan, & Yee (2018) defines organizational culture as organizational culture is unique characteristics that reflect an organization's goals and values, including assumptions, beliefs, norms, and ideas. Kangas, Kaptein, Huhtala, Lämsä, Pihlajasaari, & Feldt (2018) added that organizational culture is the ethical quality of a work environment, incorporating the experiences, presumptions, and expectations of the organization's members. Marliana (2015) concluded that organizational culture is an organizational value system adopted by members of the organization, which influences the way of working and behaving from the members of the organization.…”
Section: Organizational Culturementioning
confidence: 99%
“…Given that the aim of our study is to find out in what respect team ethical cultures differ (when they do differ), we have to use the CEV model because so far it is the only multidimensional scale of ethical culture. To preserve construct validity, the choice of the CEV model also reflects its recent use in many empirical studies on ethical culture (e.g., Huhtala et al 2015Huhtala et al , 2016Huhtala et al , 2018Kangas et al 2016Kangas et al , 2017Pučėtaitė et al 2016;Riivari and Lämsä 2014;Zaal et al 2017).…”
Section: Team Ethical Culturementioning
confidence: 99%
“…The CEV scale has received empirical evidence for broad generalizability and support for both convergent and discriminant validity. This scale has been used in different national contexts: the Netherlands (Kaptein, 2008), Finland (Huhtala, Feldt, Lämsä, Mauno, & Kinnunen, 2011;Kangas, Feldt, Huhtala, & Rantanen, 2014;Kangas, Muotka, Huhtala, Mäkikangas, & Feldt, 2015;Riivari & Lämsä, 2014;Riivari, Lämsä, Kujala, & Heiskanen, 2012), and Lithuania (Novelskaite & Pucetaite, 2014), both in longitudinal Kangas et al, 2016) and in cross-sectional studies (e.g., Huhtala, Tolvanen, Mauno, & Feldt, 2014;Kaptein, 2011), and the structure of the original scale has been widely supported by these studies (see Table 1). DeBode et al (2013) developed a shortened version of Kaptein's (2008) CEV-58 scale.…”
Section: Measuring Organizational Virtuesmentioning
confidence: 99%